Keratoacanthoma-An Unusual Presentation - Krishnan S.G.S; Yesudian Devakar P; Jayaraman M; Janaki V.R; Boopal Raj J.M (Wolters Kluwer Medknow Publications, 1999)
A 60 year old male presented with complaints of raised skin lesions over the suprapubic area which spontaneously fell off, only to recur. On examination, there were multiple verrucous, homy papules over suprapubic area. Dowling sign was positive and a clinical diagnosis of verruca vulgaris was made. But a biopsy from the lesion showed features of keratoacanthoma. Patient also had firm, discrete papules with crateriform depressions along the medical margin of palms, which can be grouped under marginal keratodermas.